Microbes : the life-changing story of germs - Peterson, Phillip K. (Prometheus Books, 2020)
"With straight-forward and engaging writing, infectious diseases physician Phillip Peterson surveys how our understanding of viruses has changed throughout history, from early plagues and pandemics to more recent outbreaks like HIV/AIDS, Ebola, and the Zika virus. Microbes also takes on contemporary issues like the importance of vaccinations in the face of the growing anti-vaxxer movement, as well as the rise of cutting-edge health treatments like fecal transplants. Microbes explains for general readers where these germs came from, what they do to and for us, and what can be done to stop the bad actors and foster the benefactors"--